Peran Ditsamapta dalam Meningkatkan Pelayanan Publik untuk Mewujudkan Polisi Republik Indonesia yang Presisi - Aprianty, Henny; Rudiyanto, George; Dani, Rahiman; Purnawan, Heru; Yanto, Hernowo Novi (Jurnal Publisitas, 2023)
The Directorate of Samapta (Ditsamapta) is a work unit at the Polda level under the Kapolda. Samapta is in charge of carrying out four activities namely Arrangement, Guard, Escort and Patrol (Turjawali). Crowd control (Dalmas). Seacrh And Rescue (SAR), as well as Animal Assistance (k-9). Samapta's main task is to carry out the function of the police as a preventive or preventive task against violations of the law or disruption of the Kamtibmas, carry out early stages of repressive action as well as other forms of disturbance of the Kamtibmas. Efforts to carry out police functions according to Law of the Republic of Indonesia Number 2 of 2002 concerning the Police of the Republic of Indonesia "that the maintenance of domestic security includes public order, law enforcement, protection, protecting the community, and service to the community is carried out by the Indonesian National Police as an instrument of the state which assisted by society by upholding human rights”. The provision of services in this case must be given special attention because it involves the interests of the people. The implementation of the same tasks influences human resources and existing facilities and infrastructure because these two factors also influence the results of the performance of officers in the field. In community service by the police carried out by the Samapta Directorate it has not been fully achieved because in carrying out tasks in the samapta function there are still a number of things that affect work in providing public services. Public services carried out by the Samapta directorate include patrol activities.